Gut Microbiome: An Intersection between Human Genome, Diet, and Epigenetics - Abdullahi Y. Muhammad; Malik Amonov; Atif A. Baig; Farrukh J. Alvi (Advanced Gut & Microbiome Research)
The composition and diversity of gut microbiome are in crosstalk with the genetic makeup and diet of an individual. Under normal health conditions, the gut commensals are in homeostasis with the host; while they inhabit the gut for their normal growth, they protect against invading pathogens through anticolonization mechanisms and contribute largely to the metabolism of several macromolecules in the gut. Specific genetic variants in genes that are responsible for maintaining the composition of the gut commensal, such as genes of the immune system, are described to result in gut dysbiosis that can lead to the development of several autoimmune diseases such as inflammatory bowel disease and type-1 diabetes. Similarly, the diet of an individual shapes the gut microbiota by allowing the predominance of microbes that metabolize an abundant macromolecule in the diet. Epigenetically, the microbial metabolites produced by these microbes can be beneficial in the treatment of cancer or deteriorating by serving as carcinogens. Therefore, the complex association of the gut microbiome with the genetic makeup and diet of an individual plays a significant role in the development of several diseases and health conditions. Recently, the association between the human genome and the gut microbiome has been analyzed and considered a multiomic approach, and extensive genome-wide association studies were conducted to further understand the complex relationship.